Lacticaseibacillus rhamnosus CBT LR5 with skim milk alleviates scopolamine-induced cognitive impairment in mice - Bae, Ho Jung; Kim, Song-In; Kim, So-Yeon; Cho, Ye Eun; Sung, Soohyun; Lim, Seokhee; Cho, Kyohee; Park, Se Jin; Lim, Sanghyun (Frontiers in Microbiology, 2025)
IntroductionEmerging evidence highlights the gut-brain axis as a pivotal pathway linking gastrointestinal health with cognitive function, particularly in neurodegenerative conditions such as Alzheimer’s disease (AD).MethodsThis study investigated the cognitive-enhancing effects of the probiotic strain Lacticaseibacillus rhamnosus CBT LR5 (LR5), alone or in combination with skim milk, in a mouse model of scopolamine-induced cognitive impairment. The cognitive functions were evaluated using the novel object recognition test (NOR) and the passive avoidance test (PAT).ResultsThe results demonstrated that the oral administration of LR5, especially when combined with skim milk, significantly ameliorated scopolamine-induced cognitive deficits. Mechanistically, treatment with LR5 combined with skim milk restored the diversity and composition of the gut microbiota increased the abundance of beneficial genera, such as Muribaculaceae and enhanced intestinal barrier integrity by increasing the expression of tight junction proteins, including claudin-1, occludin, and zonula occludens-1. Additionally, this combination reduced systemic inflammation by lowering serum TNF-α and PGE2 levels and promoted increased expression of BDNF by activating the CREB-BDNF-TrkB signaling pathway in hippocampal and cortical tissues. Furthermore, correlation analyses revealed significant associations between specific gut bacterial genera, such as Lacticaseibacillus, Turicibacter, Cryptobacteroides, Ruminococcus, and Muribaculaceae, and cognitive or inflammatory biomarkers.DiscussionCollectively, these findings suggest that the synergistic effects of L. rhamnosus CBT LR5 combined with skim milk may represent an effective dietary intervention for cognitive enhancement, potentially through gut microbiota modulation, improved barrier integrity, reduced inflammation, and enhanced neurotrophic signaling.